Tantangan Berdakwah di Era Disinformasi dan Hoaks - Ramsiah Tasruddin; Fauziah Ramdani; Arfan Sery Jusuf (Faculty of Law, Universitas Pekalongan, 2025)
The digital era has brought both new opportunities and challenges for da'wah activities. The rapid development of information technology facilitates the dissemination of da'wah messages, but at the same time, it has also given rise to a proliferation of disinformation and hoaxes that have the potential to mislead the public. This paper aims to analyze the challenges of da'wah amidst the rapid flow of information that is not always valid, and to formulate relevant strategies for da'wah (Islamic preachers) in dealing with this situation. Using a qualitative approach based on a literature review, the research results show that hoaxes not only obscure the truth but can also weaken the moral authority of da'wah and divide the community. Da'wah in the era of disinformation and hoaxes faces complex challenges due to the rapid, massive, and often unverified flow of digital information. Hoaxes disguised as religious narratives can undermine the authority of da'wah (Islamic preachers), cause polarization, and even carry legal consequences. Therefore, adaptive, critical, and digital literacy-based da'wah strategies are needed, including prioritizing information clarification, strengthening communication ethics, and building collaborative da'wah networks. Preaching in the era of disinformation requires preachers to be not only skilled in conveying religious messages but also proficient in media and technology literacy, so that their preaching remains relevant, authentic, and effective for society